PbWoxT1 mRNA from pear (Pyrus betulaefolia) undergoes long‐distance transport assisted by a polypyrimidine tract binding protein - Duan, Xuwei; Zhang, Wenna; Huang, Jing; Hao, Li; Wang, Shengnan; Wang, Aide; Meng, Dong; Zhang, Qiulei; Chen, Qiuju; Li, Tianzhong (The New phytologist, 2016)
Little is known about the mechanisms by which mRNAs are transported over long distances in the phloem between the rootstock and the scion in grafted woody plants. We identified an mRNA in the pear variety ‘Du Li’ (Pyrus betulaefolia) that was shown to be transportable in the phloem. It contains a WUSCHEL‐RELATED HOMEOBOX (WOX) domain and was therefore named Wox Transport 1 (PbWoxT1). A 548‐bp fragment of PbWoxT1 is critical in long‐distance transport. PbWoxT1 is rich in CUCU polypyrimidine domains and its mRNAs interact with a polypyrimidine tract binding protein, PbPTB3. Furthermore, the expression of PbWoxT1 significantly increased in the stems of wild‐type (WT) tobacco grafted onto the rootstocks of PbWoxT1 or PbPTB3 co‐overexpressing lines, but this was not the case in WT plants grafted onto PbWoxT1 overexpressing rootstocks, suggesting that PbPTB3 mediates PbWoxT1 mRNA long‐distance transport. We provide novel information that adds a new mechanism with which to explain the noncell‐autonomous manner of WOX gene function, which enriches our understanding of how WOX genes work in fruit trees and other species.